Relations between Immigration and Integration Policies in Europe Challenges, Opportunities and Perspectives in Selected EU Member States - Duszczyk, Maciej; Pachocka, Marta; Pszczółkowska, Dominika (Routledge Advances in European Politics, 2020)
"Written from a pan-European perspective, this book examines the decision-making processes in immigration and integration policies in Europe across decades, focusing on several key moments of Europe's postwar history. The analysis of factors taken into consideration by states in key moments of immigration policy (re)formulation shows that Europe is moving away from rational, economic arguments towards more political ones. This book contributes to the theoretical and practical debate regarding immigration and integration policies by arguing that - contrary to assumptions - immigration policy should not be treated as having precedence before integration policy. It also reflects on the growing anti-immigration sentiments as well as the securitisation and criminalisation of migration issues that are fuelled by right-wing politics. This book will be of key interest both to students and scholars of migration, the European Union, European integration, social policy, public policy, international relations, European studies, law, economics, sociology and to professionals, policy-makers, think tanks and associations in NGOs, the EU and other IOs."